Estimating body mass of sperm whales from aerial photographs - Glarou, Maria; Gero, Shane; Frantzis, Alexandros; Brotons, José María; Vivier, Fabien; Alexiadou, Paraskevi; Cerdà, Margalida; Pirotta, Enrico; Christiansen, Fredrik (Marine Mammal Science, 2022)
Funding: The authors wish to thank Fundación Biodiversidad for supporting COLCA project and all the ecovolunteers involved in the fieldwork of the Balearic Sperm Whale project. They are grateful to OceanCare (Switzerland) for their continuous support of the sperm whale research and conservation activities of the PCRI since 2008 and to Prof. Kostas Kostarelos and the University of Manchester for organizing the crowd-funding project “Nanowhales” to cofund the research expedition of 2019 along the Hellenic Trench. This paper represents HIMB and SOEST contribution nos. 1903 and 11568, respectively. Field research in Dominica was funded through a FNU fellowship for the Danish Council for Independent Researchsupplemented by a Sapere Aude Research Talent Award, a Carlsberg Foundation expedition grant, a grant fromFocused on Nature, and a CRE Grant from the National Geographic Society to S.G.; a FNU Large Frame Grant andVillum Foundation Grant to Peter T. Madsen at Aarhus University; and supplementary grants from the Arizona Cen-ter for Nature Conservation, Quarters For Conservation, the Dansk Akustisks Selskab, Oticon Foundation, and theDansk Tennis Fond. Body mass is a fundamental feature of animal physiology. Although sperm whales (Physeter macrocephalus) are the largest toothed predators on earth, body mass is seldom included in studies of their ecophysiology and bioenergetics due to the inherent difficulties of obtaining direct measurements. We used UAV‐photogrammetry to estimate the weight of free‐ranging sperm whales. Aerial photographs (23 calves, 11 juveniles, 55 nonmother adults, 13 mothers) were collected in the Eastern Caribbean and Mediterranean Sea during 2017–2020. Body length, widths, and heights (dorso‐ventral distance at 5% increments) were measured from dorsal and lateral photographs, while body volume was calculated using an elliptical model. Volume varied noticeably (12.01 ± 4.79 m3) in larger animals (>8 m), indicating fluctuations in body condition of adults and mothers. Volume was converted ...